On the role of intrinsic noise on the response of the p53-Mdm2 module. (16th September 2015) - Cruz-Rodríguez, Lídice; Figueroa-Morales, Nuris; Mulet, Roberto
Abstract: The protein p53 has a well established role in protecting genomic integrity in human cells. When DNA is damaged p53 induces the cell cycle arrest to prevent the transmission of the damage to cell progeny, triggers the production of proteins for DNA repair and if the damage can not be repaired the p53-mediated apoptotic pathway is ultimately activated. The p53-Mdm2 feedback loop seems to be the key circuit in this response of cells to damage. Measurements in individual human cells have shown that p53 and its regulator Mdm2 develop sustained oscillations over long periods of time, even in the absence of stress. Here we study three stochastic models of the p53-Mdm2 circuit. The models capture the response of the p53-Mdm2 circuit in its basal state, in the presence of DNA damage, and under oncogenic signals. They are studied through Gillespie's simulations, mean field methods and analytical approaches within the context of the linear noise approximation. While we can not discard that other sources of noise may also be important, our results compare quantitatively well with existing experimental data in single cells, supporting the relevance of the intrinsic noise in tuning cellular functions.